The concept and diagnostic criteria of primary lateral sclerosis - Wais, Verena; Rosenbohm, Angela; Petri, Susanne; Kollewe, Katja; Hermann, Andreas; Storch, Alexander; Hanisch, Frank; Zierz, Stephan; Nagel, Gabriele; Kassubek, Jan Rainer; Weydt, Patrick; Brettschneider, Johannes; et al. (Acta neurologica Scandinavica, 2017)
amyotrophic lateral sclerosis; diagnostic criteria; motor neuron disease; multi-system degeneration; primary lateral sclerosis; pringle criteria
Online veröffentlicht: November 15, 2016